Optical mineralogy - Verma, Pramod K (New Delhi : Ane Books, 2010)
Designed to be useful even after students have completed their formal optical mineralogy course, Optical Mineralogy covers advances in instrumentation and includes illustrations of minerals as seen through petrological microscopes. The initial chapters familiarize readers with essential concepts in optics and optical mineralogy, and questions at the end of each chapter provide insight into issues students will deal with the field. Containing tables that make important information easily accessible, the book highlights the importance of optical mineralogy in extracting information about the interior of crystals.
Appendices 361-368p.; Michel levy chart 369p.
Keywords: Nesosilicates; Non-silicates; Tektosilicates; Refractometry